LAMP2 exon‐copy number variations in Danon disease heterozygote female probands: Infrequent or underdetected?. Issue 11 (8th September 2018) - Majer, Filip; Piherova, Lenka; Reboun, Martin; Stara, Veronika; Pelak, Ondrej; Norambuena, Patricia; Stranecky, Viktor; Krebsova, Alice; Vlaskova, Hana; Dvorakova, Lenka; Kmoch, Stanislav; Kalina, Tomas; et al.
Abstract : Danon disease (DD) is an X‐linked disorder caused by mutations in the lysosomal‐associated membrane protein 2 ( LAMP2 ) gene ( Xq24 ). DD is characterized by cognitive deficit, myopathy, and cardiomyopathy in male patients. The phenotype is variable and mitigated in females. The timely identification of de‐novo LAMP2 mutated family members, many of whom are heterozygous females, remains critical for their treatment and family counseling. DD laboratory testing builds on minimally invasive quantification of the LAMP2 protein in white blood cells and characterization of the specific mutation. This integrative approach is particularly helpful when assessing suspect female heterozygotes. LAMP2 exon‐copy number variations (eCNVs) were so far reported only in X‐hemizygous male DD probands. In heterozygous female DD probands, the wild‐type allele may hamper the identification of an eCNV even if it results in the complete abolition of LAMP2 transcription and/or translation. To document the likely underappreciated rate of occurrence and point out numerous potential pitfalls of detection of the LAMP2 eCNVs, we present the first two DD heterozygote female probands who harbor novel multi‐exon LAMP2 deletions. Critical for counseling and recurrence prediction, we also highlight the need to search for somatic‐germinal mosaicism in DD families.